Penerapan Religious Culture Melalui Pembiasaan Membaca Al-Qur’an Dan Shalat Dhuha Di Madrasah Tsanawiyah - Lubis, Dwi Muthia Ridha; Siahaan, Amiruddin; Salminawati, Salminawati (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2023)
This study aims to describe, analyze programs, analyze implementation, analyze supporting and inhibiting factors and analyze the implications of implementing religious culture through the habit of reading the Koran and praying dhuha for students at MTs Nurus Salam Deli Tua. This research is a descriptive qualitative research with a phenomenological approach. Data collection techniques are carried out through the process of observation, interviews and also documentation. Then the data obtained is presented through the process of data reduction (data reduction), data presentation (data display), and drawing conclusions (verification). The results of the research show that: 1) There are several stages that must be planned, namely determining a program with objectives and foundations; determining the success of the Religious Culture program; determine the person in charge; Organize activities and schedule activities. 2) the implementation of the Duha prayer which is carried out in congregation in the morning, then prayer and dhikr together, brief tausiyah, second, the implementation of reading the Al-Qur'an which is carried out in each class guided by the subject teacher. With the teacher's method of listening to students' reading. 3) Supporting factors in the Religious Culture program are school regulations, coaching staff, facilities and infrastructure, while factors are students' self-awareness, the number of sins and immorality. 4) The implications of the Religious Culture program, namely Uniting Allah SWT in Rububiah and Uluhiyah; being solemn in prayer; Focus on reading the Qur'an; Sincere; It's easy to do good and obey, it's hard to do God's prohibition; The heart and soul are calm, far from anxiety; Honest; Humble; Discipline; and Manners.